Functional analysis of African Xanthomonas oryzae pv. oryzae TALomes reveals a new susceptibility gene in bacterial leaf blight of rice. - Tuan T Tran; Alvaro L Pérez-Quintero; Issa Wonni; Sara C D Carpenter; Yanhua Yu; Li Wang; Jan E Leach; Valérie Verdier; Sébastien Cunnac; Adam J Bogdanove; Ralf Koebnik; Mathilde Hutin; et al. (PLoS Pathogens)
Most Xanthomonas species translocate Transcription Activator-Like (TAL) effectors into plant cells where they function like plant transcription factors via a programmable DNA-binding domain. Characterized strains of rice pathogenic X. oryzae pv. oryzae harbor 9-16 different tal effector genes, but the function of only a few of them has been decoded. Using sequencing of entire genomes, we first performed comparative analyses of the complete repertoires of TAL effectors, herein referred to as TALomes, in three Xoo strains forming an African genetic lineage different from Asian Xoo. A phylogenetic analysis of the three TALomes combined with in silico predictions of TAL effector targets showed that African Xoo TALomes are highly conserved, genetically distant from Asian ones, and closely related to TAL effectors from the bacterial leaf streak pathogen Xanthomonas oryzae pv. oryzicola (Xoc). Nine clusters of TAL effectors could be identified among the three TALomes, including three showing higher levels of variation in their repeat variable diresidues (RVDs). Detailed analyses of these groups revealed recombination events as a possible source of variation among TAL effector genes. Next, to address contribution to virulence, nine TAL effector genes from the Malian Xoo strain MAI1 and four allelic variants from the Burkinabe Xoo strain BAI3, thus representing most of the TAL effector diversity in African Xoo strains, were expressed in the TAL effector-deficient X. oryzae strain X11-5A for gain-of-function assays. Inoculation of the susceptible rice variety Azucena lead to the discovery of three TAL effectors promoting virulence, including two TAL effectors previously reported to target the susceptibility (S) gene OsSWEET14 and a novel major virulence contributor, TalB. RNA profiling experiments in rice and in silico prediction of EBEs were carried out to identify candidate targets of TalB, revealing OsTFX1, a bZIP transcription factor previously identified as a bacterial blight S gene, and OsERF#123, which encodes a subgroup IXc AP2/ERF transcription factor. Use of designer TAL effectors demonstrated that induction of either gene resulted in greater susceptibility to strain X11-5A. The induction of OsERF#123 by BAI3Δ1, a talB knockout derivative of BAI3, carrying these designer TAL effectors increased virulence of BAI3Δ1, validating OsERF#123 as a new, bacterial blight S gene.